Asset quality and performance: an empirical study of Indian microfinance institutions. (14th October 2019) - Ray, Sougata; Mahapatra, Sushanta Kumar
The objective of the study is to analyse the impact of the asset quality on the financial performance of the Indian microfinance institutions. Using the financial data of 76 'for-profit' Indian MFIs from the microfinance information exchange database for the period 2006 to 2013, we observe that the quality of asset deteriorated significantly during the period of study and it has impacted the performance of the MFIs negatively. The commercialisation of the MFIs resulted in predatory lending and unfair debt collection practices ensuring better repayment rates. These practices, however, resulted in client defaults and an increase in both portfolio-at-risk and write-off ratio. The study, therefore, suggests that the MFIs need to re-examine and realign their operations so that social parameters are given due importance in every aspect of lending activity. This will ensure that MFIs achieve their social objective as well as ensure higher repayment rates.